Development of sandwich panels of customized functionalities for the rehabilitation of the built patrimony - Costa, Pedro A. B. Sá e (2015)
Considering that the future of the construction sector in most European countries will mainly lie in the renovation of the existing building stock, in the next coming years thousands of energy inefficient buildings will need renovation to force EU member states to reach the EU 2020 targets and implement the Energy Performance of Buildings Directive (EPBD). Seeing the actual crisis in the construction sector as an opportunity, this work aims to develop a concept for prefabricated customizable sandwich panels for the multifunctional renovation of buildings, focusing also on technological innovation. More than a conventional solution, this proposal aims to combine sustainable and recycled building materials, available technologies and systems with advanced design and manufacturing tools within an integrated and mass-customizable approach of advanced building renovation prefabricated solutions. The adoption of these new proposed solutions would improve the living standards of the inhabitants of our cities, reducing energy inefficiency and other existing construction/renovation problems, while enabling some advanced features like the incorporation of technical modules that could even monitor the building performance during its full lifetime and the living conditions of its occupants.